Performance assessment of bank XYZ DKI Jakarta branch using the balanced scorecard approach in the pandemi era of Covid 19 - Purwanta, Putri Ayu; Siregar, Hermanto; Bandono, Bayu (Universitas Aisyah Pringsewu, 2023)
This research is motivated by the decline in the performance of Islamic banks in Indonesia due to the covid 19 pandemic. This is interesting for researchers to conduct research that aims to analyze the performance assessment of XYZ banks before and during the covid 19 pandemic era and the influence of a customer perspective, internal business process perspective, as well as a learning and growth perspective on bank financial performance XYZ. The research method used is the balanced scorecard approach and multiple regression analysis. The analysis tools used are Microsoft Excel and SPSS software. The data used are primary data in the form of questionnaires and interviews as well as secondary data in the form of Bank XYZ's 2008-2021 financial reports. The results of the study show that the performance assessment of Bank XYZ using the balanced Ascorecard method before and during the pandemic was not maximized because it was still below a score of 4. The effect of the customer perspective on financial performance is negative where the higher the customer perspective with indicators of third party funds that far exceed financing indicators, the lower financial performance. The influence of the internal business process perspective on financial performance is negative where the higher the internal business process perspective with indicators of the number of offices and ATMs, the lower the financial performance in terms of efficiency. The influence of the learning and growth perspective on financial performance is positive where the higher the learning and growth perspective with indicators of employee productivity, the financial performance will improve. Abstrak: Penelitian ini dilatarbelakangi oleh penurunan kinerjaAbank syariah di Indonesia akibat pandemi covid 19. Hal ini menarik peneliti melakukan penelitian yang bertujuan untuk menganalisis penilaian kinerja bank XYZ sebelum dan era pandemi covid 19 serta pengaruhAperspektif pelanggan, perspektif prosesAbisnis internal, serta perspektif pembelajaran dan pertumbuhan terhadap kinerjaAkeuangan Bank XYZ. MetodeApenelitian yang digunakan dengan pendekatan A balanced scorecard dan analisisAregresi berganda. Alat analisis yang digunakan adalah software microsoft excel dan SPSS. DataAyang digunakan adalahAdata primer berupa kuesionerAdan wawancara serta dataAsekunder berupa laporan keuangan Bank XYZ tahun 2008-2021. HasilApenelitian menunjukkanAbahwa Penilaian kinerja Bank XYZ dengan metode balancedAscorecard sebelum dan saat pandemi belum maksimal karena masih di bawah skor 4. Pengaruh perspektifApelanggan terhadap kinerjaAkeuangan adalah negatif dimana semakin tinggi perspektifApelanggan dengan indikator dana pihak ketiga yang jauh melebihi indikator pembiayaan maka akan menurunkan kinerjaAkeuangan. Pengaruh perspektif prosesAbisnis internal terhadap kinerja keuangan adalah negatif dimana semakin tinggi perspektif proses bisnis internal dengan indikator jumlah kantor dan ATM maka akan menurunkan kinerja keuangan dalam rangka efisiensi. Pengaruh perspektif pembelajaran dan pertumbuhan terhadap kinerja keuangan adalah positif dimana semakin tinggi perspektif pembelajaran dan pertumbuhan dengan indikator produktivitas karyawan maka akan meningkatkan kinerja keuangan.